Nilai-Nilai Edukatif Al-Qur’an Surat Ar-Rum Ayat 21 Dalam Membangun Rumah Tangga Sakinah Mawaddah Wa Rahmah Kajian Ilmu Pendidikan Islam - Sofiawati, Eva; Suhada, Dede (STAI Al-Musaddadiyah Garut, 2024)
The Qur'an literally means recitation that reaches the peak of perfection that provides guidance to all human beings in matters of tashri', creed, and morals to achieve happiness in this world and the hereafter. The Qur'an is considered a fundamental book of education in Islam, providing comprehensive instructions and guidelines in various aspects of Muslim life. As a divine revelation revealed to Prophet Muhammad SAW, the Qur'an functions not only as a source of law and worship, but also as a moral and ethical guidebook. The Qur'an also provides principles of character education that include honesty, justice, and compassion. This research aims to find out 1). The meaning of Islamic Education, 2). The educational values of Al-Qur'an Surah Ar-Rum verse 21 in building a sakinah mawaddah wa rahmah household in the study of Islamic Education. This research is a type of library research, namely by conducting in-depth studies and research from various Islamic literature, both from primary sources; namely Al-Qur'an surah Ar-Rum verse 21 along with a review of its interpretation, and secondary sources; namely books or books that can support this research along with a review of Islamic Education. The research method used is qualitative method. The research method used is a qualitative method by focusing on content analysis of Al-Qur'an Surah Ar-Rum Verse 21 and the content of book texts. The results of this study indicate that the educational values of the Qur'an in Surah Ar-Rum verse 21 consist of i'tiqadiyah values (faith), khuluqiyah values (morals), and amaliyah values (daily behaviour). These values form the basis for building a household full of sakinah, mawaddah, and wa rahmah, with the cooperation of husband and wife in solving problems and feeling happiness in the household. The educational value in Al-Qur'an Surah Ar-Rum Verse 21 Islamic Education Science Study is to form and strengthen the poundation of the family, thus creating a harmonious and blessed household according to Islamic teachings. Keywords: Educative Values, Al-Qur'an, Islamic Education.